Factors of Work Motivation, Work Environment, and Organizational Commitment Affecting the Job Performance of Employees of the Bank for Agriculture and Agricultural Cooperatives (BAAC) in Nakhon Ratchasima Province - Kaewkhunyo, Ong-art; Chamchong, Anuchat (Journal of MCU Phetchaburi Review, 2025)
This study aimed to examine the factors of work motivation, work environment, and organizational commitment that affect the job performance of employees of the Bank for Agriculture and Agricultural Cooperatives (BAAC) in Nakhon Ratchasima Province. The research employed a quantitative approach. Data were collected through questionnaires administered to 400 BAAC employees working in 35 branches across the province. The data were analyzed using mean and standard deviation, as well as multiple regression analysis to test the hypotheses at a statistical significance level of 0.05. The results revealed that, overall, the studied factors—work motivation, work environment, and organizational commitment—had a significant influence on the job performance of BAAC employees in Nakhon Ratchasima Province.